THE EFFECT OF TRUST AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT BANK RAKYAT INDONESIA (BRI) TINAMBUNG BRANCH IN POLEWALI MANDAR REGENCY - Alfiranti,; Nur Qamariah S,; Nursyam Anwar, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The Influence of Trust and Service Quality on Customer Satisfaction at Bank Rakyat Indonesia (BRI) Tinambung Branch, Polewali Mandar Regency. This study aims to determine the influence of Trust and Service Quality on Customer Satisfaction at Bank Rakyat Indonesia (BRI) Tinambung Branch, Polewali Mandar Regency. The type of research used is quantitative research with a descriptive approach, where descriptive research is used to explain numerical results and hypothesis testing. The data sources used in this study are primary data sources and secondary data sources with a total of 75 respondents. Data collection techniques using observation and questionnaires with multiple linear regression analysis techniques. Data processing using SPSS version 25. The results of the study showed that the Trust variable has a positive and significant effect on Customer Satisfaction. From the results of testing the Service Quality variable has a positive and significant effect on Customer Satisfaction. Furthermore, Trust and Service Quality together have a positive and significant effect on Customer Satisfaction at Bank Rakyat Indonesia (BRI) Tinambung Branch, Polewali Mandar Regency.